Case Report: A Case of Moyamoya Syndrome Associated With Multiple Endocrine Neoplasia Type 2A - Matano, Fumihiro; Murai, Yasuo; Watanabe, Atsushi; Shirokane, Kazutaka; Igarashi, Takehito; Shimizu, Kazuo; Shimada, Takashi; Morita, Akio (Frontiers in Endocrinology, 2021)
We report for the first time a case of MEN2A complicated by moyamoya syndrome. A 52-year-old woman presented with vertigo. Magnetic resonance angiography (MRA) revealed bilateral supraclinoid stenosis of the internal carotid artery and abnormal moyamoya-like vessels around the basal ganglia. She had a heterozygous variant of RNF-213, which is the susceptibility gene for moyamoya disease. She had also previously received diagnoses of medullary thyroid carcinoma (MTC) at age 23 and left-sided pheochromocytoma (PHEO) at age 41. Genetic testing revealed heterozygosity for a mutation at codon 634 in exon 11 (TGC-TTC mutation; p.Cys634Phe) of the Ret gene. We speculate that the moyamoya-like structure of the vessels resulted from excessive catecholamine secretion caused by MEN2A or a genetic mutation of RNF231. Physicians should recognize that MEN2A can be present with moyamoya syndrome.